The Effect of Using Digital Comic Strips in Reading on Young Learners - Ni Putu Ayu Puspa Yuliandari (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to investigate the effect of using digital comic strips in teaching English reading text at SDN 3 Banjar Jawa by using Comic & Meme Creator. A quasi-experimental by pre-test and post-test non-equivalent control group was applied as a design for the study. The sample of the study was two classes in third grade (III A and III B) that consisted 30 students for each class. The data were processed by using SPSS 24.0 to analyze paired sample t-test. The finding of the study shown the significant effect on students’ English reading score by using digital comic strips. The data of paired sample t-test shown the mean of post-test on treatment class was 84 and control class was 77. The hypothesis testing of treatment class showed -10.698 and the score of sig. (2-tailed) is 0.000. According to the null hypothesis (Ho) which the score is 0.05, the score of sig. (2-tailed) of the data was smaller than the Ho. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (H⍺) was accepted. In conclusion, there is a significant effect of using digital comic strips in teaching English reading text at SDN 3 Banjar Jawa.